PENGARUH KOMITMEN ORGANISASIONAL DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT TELKOM AKSES AREA SUMATERA UTARA PEMATANG SIANTAR - Harefa, Frans Eka Putra; Sitanggang, Darna (Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study is to determine the influence of organizational commitment and working discipline towards employees achievement at PT. Telkom Access Pematang Siantar, North Sumatera Territory. The analytical method that was used is multiple linear regression analysis. The amount of population in this study is 284 employees working PT. Telkom Access Pematang Siantar, North Sumatera Areal . The sampling amount is 166 respondens by using Proportional Random Sampling. The data was collected by using questionnaire, interview, and documentation study. From the result of the research, it is discovered that the coefficient of determination (R Square) is 0,820 or 82%. This means that the variations in employee working performance can be determined by variations in organizational commitment and working discipline by 82%, while the rest 18% is determined by other variables not included in this research, such as motivation, leadership, communication, and training program. The multiple linear regression equation obtained from the data processing result is Y = 4.182 + 0.420 (X1) + 0.615 (X2) + ei, which means that organizational commitment and working discipline are positively affecting the employee performance at PT. Telkom Access Pematang Siantar, North Sumatera Territory. Simultaneously, organizational commitment and working discipline are significantly affecting the employees achievement at PT. Telkom Access Pematang Siantar, North Sumatera Areal. Partial Testing shows that organizational commitment and work discipline are having a positive and significant result on employees achievement at PT. Telkom Access Pematang Siantar, North Sumatera Areal. Meanwhile, working discipline is the most influencing variable towards employees achievement at PT. Telkom Access Pematang Siantar, North Sumatera Areal, with higher regression coefficient value which is 0,615. This suggests the company to give their attention to organizational commitment and work discipline, because both of those variables are positively and significantly affecting employees performance.